Impact Of Multimedia Package On Motor Deficiencies Among Children With Autism Reference To Family (International Journal of Food and Nutritional Sciences, 2022)
A large number of children with autism are observed with btosome motor deficiencies. Fine and gross motor deficiencies can lead to low self-esteem, underachievement, frustration, and stress in affected children. The main aim of this research is to multimedia systematically package training prog that rams given to affected children with autism to improve the fine and gross motor deficiencies in children and to assess the effectiveness of multimedia packages. Some systematic reviews were collected for the evidence. The experimental method was applied for this research. A single-group pre-test and post-test group design were used. The sample consists for the experiment were 32 children with autism (8–15) available in Rejoice School for Autism and Developed mentally delayed Nagercoil. The observation method was followed. The scale on motor deficiencies among children with autism about family was developed and validated by the investigator. The result shows the effective use of multimedia packages in reshaping the motor deficiencies among children with autism under the categories mild, moderate, and severe. The effect of the training session was maintained as a follow-up.